Pengaruh Kontrol Sosial Di Masyarakat Dengan Kewenangan Aparat Penegak Hukum Terhadap Efektifitas Keberlakuan Hukum Di Indonesia - Marlina Dea Dea; Kris Yunianto; Dimas Yeni; Anita Trisiana (RESEARCH FAIR UNISRI, 2020)
Social control was an attempt the act of preventing deviation social in the community to set the community, having attitude, value, and norma prevailing. This study attempts to know how to control social in the community pertaining by law enforcement officials to the effectiveness of legal enactment in indonesia, where law enforcement officials are required is just and honest in enforcing law. This research uses the method descriptive analysis.The community advanced should be to comply with the law, because it law very helpful human life every day to set human life.